Implementation of novel agro-climatic services help more than 500,000 farmers in Colombia, Honduras, Guatemala and Nicaragua better plan their crops - CGIAR Research Program on Climate Change, Agriculture and Food Security (2018)
CCAFS scientists developed, tailored and implemented actions to support the implementation of climate services for Agriculture in Colombia, Nicaragua, Honduras and Guatemala. These include the creation of 22 Local Technical Agroclimatic Committees (LTACs), the automation of the Climate Predictability Tool, and the development of capacities in Ministries of Agriculture, farmers organizations, and meteorological services. We compiled evidence to demonstrate that these developments have resulted in 500.000 farmers being able to access agro-climatic information for planning their crops. This achievement is also part of the implementation of the Regional Strategy for Disaster Risk Management in the Agriculture Sector and Food and Nutrition Security in Latin America and the Caribbean (2018–2030), which prioritized as a key action the implementation of the LTAC approach across the region.